Determinants of sickness absence rate among Finnish municipal employees - Tiina Vuorio; Sakari Suominen; Hannu Kautiainen; Päivi Korhonen (Taylor & Francis Group, 2019)
Objective: In addition to acute health problems, various aspects of health behavior, work-related and sociodemographic factors have been shown to influence the rate of sickness absence. The aim of this study was to concomitantly examine factors known to have an association with absenteeism. We hypothesized the prevalence of chronic diseases being the most important factor associated with sickness absence. Design: A cross-sectional study. Setting: Occupational health care in the region of Pori, Finland. Subjects: 671 municipal employees (89% females) with a mean age of 49 (SD 10) years. Information about the study subjects was gathered from medical records, by physical examination and questionnaires containing information about physical and mental health, health behavior, work-related and sociodemographic factors. The number of sickness absence days was obtained from the records of the city of Pori. Main outcome measures: The relationship of absenteeism rate with sociodemographic, health- and work-related risk factors. Results: In the multivariate analysis, the mean number of chronic diseases (IRR 1.24, 95% CI 1.13 to 1.36), work ability (IRR 0.83, 95% CI 0.76 to 0.91), and length of years in education (IRR 0.90, 95% CI 0.85 to 0.95) remained as independent factors associated with absenteeism. Conclusion: According to our results, chronic diseases, self-perceived work ability and length of years in education are the most important determinants of the rate of sickness absence. This implies that among working-aged people the treatment of chronic medical conditions is also worth prioritizing, not only to prevent complications, but also to avoid sickness absences. KEY POINTS Various sociodemographic, health- and work- related risk factors have been shown to influence sickness absence. The study aimed to find the most important determinants of absenteeism among several known risk factors in Finnish municipal employees. Chronic diseases, self-perceived work ability and education years remained as the most important determinants of sickness absence rates. Treatment of chronic medical conditions should be prioritized in order to reduce sickness absence rate.